Determination of Urinary Creatinine in Washington State Residents via Liquid Chromatography/Tandem Mass Spectrometry - Caroline E. West; Blaine N. Rhodes (International Journal of Analytical Chemistry)
A viable, quick, and reliable method for determining urinary creatinine by liquid chromatography/tandem mass spectrometry (LC/MS/MS) was developed and used to evaluate spot urine samples collected for the Washington Environmental Biomonitoring Survey (WEBS): part of the Washington State Department of Health, Public Health Laboratories (PHL). 50 µL of urine was mixed with a 1 : 1 acetonitrile/water solution containing deuterated creatinine as the internal standard and then analyzed by LC/MS/MS. Utilizing electrospray ionization (ESI) in positive mode, the transition ions for creatinine and creatinine-d3 were determined to be 114.0 to 44.1 (quantifier), 114.0 to 86.1 (qualifier), and 117.0 to 47.1 (creatinine-d3). The retention time for creatinine was 0.85 minutes. The linear calibration range was 20–4000 mg/L, with a limit of detection at 1.77 mg/L and a limit of quantitation at 5.91 mg/L. LC/MS/MS and the colorimetric Jaffé reaction were associated significantly (Pearson r=0.9898 and R2=0.9797, ρ≤0.0001). The LC/MS/MS method developed at the PHL to determine creatinine in the spot urine samples had shorter retention times, and was more sensitive, reliable, reproducible, and safer than other LC/MS/MS or commercial methods such as the Jaffé reaction or modified versions thereof.